Hubungan Kebiasaan Makan Pagi dan Aktivitas Fisik dengan Status Gizi pada Siswi SMA Muhammadiyah 1 Surakarta - Pramesti, Alfinda Diah A; , Endang Nur Widyaningsih, S.ST.,M.Si,Med (2016)
Nutritional status is determined by two things which are the fulfillment of all nutrition from food needed by body and the role of factors that determine the needs, absorption, and the use of nutrients. Breakfast calorie intake has the biggest impact in the daily intake. Physical activity also can affect nutritional status. Excess energy intakes that are not matched the energy expenditure will cause weight gain. The purpose of this research was to assess the correlations between breakfast habit, physical activity, and nutritional status in student of Muhammadiyah 1 High School at Surakarta. This research used observational with cross-sectional design. The respondents were chosen through simple random sampling from X grader who fullfilled the inclusion criteria and there were 40 respondents in total. Breakfast habit was obtained through Food Record 24 hours, physical activity was obtained through International Physical Activity and nutrition status was obtained through Body Mass Index (BMI). Data was analyzed with Pearson Product Moment test. Most of student, about 69,23%, have good breakfast habits. Physical activity of all student is moderate. Nutritional status of student mostly is normal which are 71,8% but some of them are not normal which are 28,2% with the tendency of overweight. There is no correlation between breakfast habit and nutrition status among girls in Muhammadiyah 1 High School at Surakarta (p=0,205).. There is correlation between physical activity and nutrition status among girls in Muhammadiyah 1 High School at Surakarta (p=0,000).